Pengaruh Pemberian Pupuk Organik Kaya Nitrogen terhadap Sifat Kimia Tanah Podsolik dan Pertumbuhan Tanaman Jagung (Zea mays L.) - Gusti Mutia Rusdiana; Hairil Ifansyah; Fadly Hairannoor Yusran (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
Ultisols is the dominant soil type occupies dry land areas in Indonesia. This soil type is a great potential for the development of the agricultural sector in Indonesia. Constraints of physical, chemical, and biological properties of Ultisols must be considered in utilizing for optimal development of agricultural production. This study aimed to determine the effect of inorganic and organic fertilizers in soil pH, exchangeable-Al, CEC, plant dry weight, and N uptake of maize planted on an Ultisols. This research was carried out in February to June 2021 and conducted in a greenhouse and Soil Physics and Chemistry Laboratory, Department of Soil, Faculty of Agriculture, Lambung Mangkurat University. The data obtained from all observed variables were analyzed using orthogonal contrast. The results showed that the application of fertilizer, either inorganic and organic, were able to increase soil pH, but decreased plant N uptake and plant dry weight. The application of inorganic fertilizers increased soil pH more than the application of organic, but the N uptake and dry weight of plants increased more due to the application of organic fertilizers than the inorganic. The application of ZA fertilizer decreased soil pH more than the application of urea, although the changes in exchangeable-Al, CEC, N uptake, and plant dry weight were not different. The application of green manure was able to increase the exchangeable-Al content and reduce the N uptake of plants than the application of manure.